2022
DOI: 10.1038/s41598-022-23691-y
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of stacking-fault expansion in 4H-SiC PiN diodes using proton implantation to solve bipolar degradation

Abstract: Abstract4H-SiC has been commercialized as a material for power semiconductor devices. However, the long-term reliability of 4H-SiC devices is a barrier to their widespread application, and the most important reliability issue in 4H-SiC devices is bipolar degradation. This degradation is caused by the expansion of single Shockley stacking-faults (1SSFs) from basal plane dislocations in the 4H-SiC crystal. Here, we present a method for suppressing the 1SSF expansion by proton implantation on a 4H-SiC epitaxial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…To apply the proton implantation method in SiC devices, we fabricated PiN diodes with proton implantation. 46) Although we have also performed proton implantation during or after the PiN diode fabrication processes, the fabricated diodes have exhibited significantly high on-resistance, as reported in previous studies. [63][64][65] This increase of on-resistance would be caused by trapping of electrons and reduction of the electron mobility due to defects induced by damages of the proton implantation.…”
Section: Suppression Effects On 1ssf Expansion In Pin Diodesmentioning
confidence: 66%
See 2 more Smart Citations
“…To apply the proton implantation method in SiC devices, we fabricated PiN diodes with proton implantation. 46) Although we have also performed proton implantation during or after the PiN diode fabrication processes, the fabricated diodes have exhibited significantly high on-resistance, as reported in previous studies. [63][64][65] This increase of on-resistance would be caused by trapping of electrons and reduction of the electron mobility due to defects induced by damages of the proton implantation.…”
Section: Suppression Effects On 1ssf Expansion In Pin Diodesmentioning
confidence: 66%
“…62) Based on these insights, our study focused on proton implantation, a technique already used extensively in semiconductor processes. 43,[45][46][47] 4. Proton implantation…”
Section: Our Strategy To Solve Bipolar Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the critical issues that hinder the widespread use of SiC power devices is the bipolar degradation phenomenon. [17][18][19][20][21] SiC bipolar devices such as pin diodes and insulated gate bipolar transistors face problems with defect-related degradation, in which the forward voltage is degraded due to the spontaneous expansion of single Shockley-type stacking faults (SFs) in the epitaxial layer during forward bias application. The SFs expand from basal plane dislocations (BPDs) to accommodate the glides of partial dislocations.…”
mentioning
confidence: 99%
“…35,36) Recently, we have reported that proton irradiation, which is commonly used in semiconductor processing, can suppress SF expansion in the SiC epitaxial layer driven by ultraviolet (UV) illumination and forward bias application. 21,37) Although we carefully separated the effect of change in carrier lifetimes on the driving force of SF expansion and the effect of the pinning of dislocations by proton implantation, the relationship between dislocation mobility and proton implantation has remained unclear. In the present study, we investigated the contraction behavior of SFs subjected to proton implantation and revealed the relationship between dislocation mobility and proton implantation.…”
mentioning
confidence: 99%